Classical Legacy and Its Influence as Focused in Today’s Studies in Graeco-Roman Art History - Trofimova, Anna A. (Actual Problems of Theory and History of Art, 2015)
As it comes from the ideas of the leading theorists of art, in the course of the 20th century the category of “Classical” became a key-concept in understanding the development of West-European art. Today’s studies in the history of Greek and Roman art meet the problem of its influence, its chronological and spatial transformations. The paper gives an overview of main trends and milestones in art history about Classical antiquity and its legacy telling us in details about today’s scholarly activity at the Hermitage Department of Classical Antiquities. “Classical” expansion to the periphery of oecumene, to the North Pontic area, has been remaining in focus of investigations held by the Russian scientific school. The author points out main characteristic features of the Black Sea version of ancient art, analyzes the patterns of its development, determining the role of the region as a mediator of artistic tradition, not only between peoples, but also between two historic stages of civilization. The second scholarly direction covers Hellenistic studies searching into interaction and conformity between Greek and Oriental art and cultures of Asian countries. The newest field of research is an actively developing history of restoration, while the significant specificity of the Hermitage collection is that the historical restoration should have been preserved in their places.
Keywords: historiography of Greek and Roman art history; classical legacy and its influence; Hellenistic age; Greek colonies in the North Pontic Area; department of Classical Antiquities of the State Hermitage Museum; history of restoration